Islamisasi di Wilayah Indochina: Proses Penyebaran Islam di Wilayah Kamboja, Laos, dan Vietnam - Ahmad Wildan Syidad (AN NUR: Jurnal Studi Islam, 2023)
Indochina was divided into three main regions namely Cambodia, Laos and Vietnam. These three countries were countries where the majority of the population adheres to the Buddhist belief system or religion. Islam was a very minority religion in these three countries. This article aimed to explain how the process of Islamization in the Indochina region. This research used qualitative research methods by focusing on literature studies through historical methods with three stages, namely heuristics, source criticism, interpretation, and historiography. The results of this study indicated that the process of Islamization in Cambodia which was initially welcomed by the king and local people went through the dark period of the red Khemr regime and finally the Muslim community in Cambodia was free and they rebuilt their religious system, so that the latter could live hand in hand with other religions. The process of Islamization in Laos was engaged in trading and managing butcher shops. They lived in the jami' mosque in Vientiane. Meanwhile, the process of Islamization in Vietnam started from the kingdom of Champa. There were several theories which state that the process of the arrival of Islam in Vietnam started from the relationship carried out by the crew of the Champa royal ship with traders from Brunei and Banten (Indonesia).